#$&* course Mth 158 6/20/13 9:00 pm If your solution to stated problem does not match the given solution, you should self-critique per instructions at http://vhcc2.vhcc.edu/dsmith/geninfo/labrynth_created_fall_05/levl1_22/levl2_81/file3_259.htm.
.............................................
Given Solution: * * ** 36x^2-9 is the difference of two squares. We write this as (6x)^2-3^2 then get (6x-3)(6x+3), using the special formula difference of two squares. ** &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): Factoring it out like that is a bit different than how I learned to do it, but I do see that it is much easier to explain. ??? Is how I am doing it still acceptable? ------------------------------------------------ Self-critique Rating: 3 ********************************************* Question: R.5.32 \ 28 (was R.6.24) What do you get when you factor 25 x^2 + 10 x + 1 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: It did not look obviously like any kind of special case, so I decided to use the A, B, C method. I identified A = 25 B = 10 C = 1 meaning AC = 25 I looked for factors of 25: 25, 1 ; 5, 5 (Because B is positive, I knew that I was not looking for factors that would both be positive) Then I looked to see if any of those factors would add up to B; the second set, 5 and 5, are equal to 10 25 x^2 + 10 x + 1 = 25 x^2 + 5x + 5x + 1 = (25 x^2 + 5x )+ (5x + 1) = I used the grouping method 5x (5x + 1) + 1 (5x + 1) = Even though it is understood, I wrote out a factored one so that the next steps would be more clear to see (5x + 1) (5x + 1) (5x + 1) = ( 5x + 1 )^3
.............................................
Given Solution: * * ** STUDENT SOLUTION: x^2+10x+1 is prime because there are no integers whose product is 10 and sum is 1 INSTRUCTOR COMMENTS: The sum should be 10 and the product 1. I agree that there are no two integers with this property. Furthermore there are no two rational numbers with this property. So you would never be able to find the factors by inspection. However that doesn't mean that there aren't two irrational numbers with the property. For example 10 and 1/10 come close to the criteria, with product 1 and sum 10.1. The quadratic formula tells you in fact that the two numbers are ( -10 + sqrt( 10^4 - 4 * 1 * 1) ) / (2 * 1) and ( -10 - sqrt( 10^4 - 4 * 1 * 1) ) / (2 * 1) . Since 10^2 - 4 = 96 is positive, these are real numbers, both irrational. So the polynomial isn't prime. ** &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ??? I am a little confused. Did I use the A, B, C thing incorrectly? ------------------------------------------------ Self-critique Rating: 1 ********************************************* Question: R.5.34 (was R.6.30). What do you get when you factor x^3 + 125 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: x^3 + 125 is the sum of two cubes (x + 5) (x^2 - 5x + 25) confidence rating #$&*: 3 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: x^3+125 is the sum of two cubes, with 125 = 5^3. We know that a^3 + b^3 = (a+b) ( a^2 - 2 a b + b^2). So we write x^3+5^3 = (x+5)(x^2-5x+25). &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): OK ------------------------------------------------ Self-critique Rating: OK ********************************************* Question: R.5.46 (was R.6.42). What do you get when you factor x^2 - 17 x + 16 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: I had to first find all the pairs of integers whose product was 16 Pairs 1, 16 -1, -16 2, 8 -2, -8 4, 4 -4, -4 Sum 17 -17 10 -10 8 -8 The pair -1 and -16 have a product of 16 and a sum of -17 so x^2 - 17 x + 16 = (x - 1) (x - 16) confidence rating #$&*: 3 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: * * ** x^2-17x+16 is of the form (x + a) ( x + b) = x^2 + (a + b) x + ab, with a+b = -17 and ab = 16. If ab = 16 then, if a and b happen to be integers, we have the following possibilities: a = 1, b = 16, or a = 2, b = 8, or a = -2, b = -8, or a = 4, b = 4, or a = -1, b = -16, or a = -4, b = -4. These are the only possible integer factors of 16. In order to get a + b = -17 we must have at least one negative factor. So the possibilities are reduced to a = -2, b = -8, or a = -1, b = -16, or a = -4, b = -4. The only of the these possibilities that gives us a + b = -17 is a = -1, b = -16. So we conclude that x^2 - 17 x + 16 = (x-16)(x-1). ** &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): OK ------------------------------------------------ Self-critique Rating: OK ********************************************* Question: R.5.52 (was R.6.48). What do you get when you factor 3 x^2 - 3 x + 2 x - 2 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: For this problem you must factor by grouping 3 x^2 - 3 x + 2 x - 2 = (3 x^2 - 3 x ) + (2 x - 2) = 3x (x-1) + 2 ( x-1) = (3x + 2) (x - 1) confidence rating #$&*: 3 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: * * ** This expression can be factored by grouping: 3x^2-3x+2x-2 = (3x^2-3x)+(2x-2) = 3x(x-1)+2(x-1) = (3x+2)(x-1). ** ADDITIONAL EXPLANATION: To see that (3x^2-3x)+(2x-2) = 3x(x-1)+2(x-1) apply the distributive law to each term in the second expression: 3x ( x - 1) = 3 x^2 - 3x, and 2 ( x - 1) = 2x - 2. To see that 3x(x-1)+2(x-1) = (3x+2)(x-1) apply the distributive law as follows: (3x + 2) ( x - 1) = 3x * (x - 1) + 2 * (x - 1). &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): OK ------------------------------------------------ Self-critique Rating: OK ********************************************* Question: R.5.64 (was R.6.60). What do you get when you factor 3 x^2 - 10 x + 8 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: Comparing it to Ax^2 + Bx + C we find that A= 3 B = -10 and C = 8 The value of AC = 24 We must find the pair of integers that result in 24 as their product; the possibilities are 1, 24; -1, -24; 2, 12; -2, -12; 3, 8; -3, -8; 4, 6; and -4, -6 We must find which of these pairs adds up to B. -4 and -6 result in a sum of -10 Applying this, 3 x^2 - 10 x + 8 = 3 x^2 - 4x - 6x + 8 = (3 x^2 - 4x) + (-6x + 8) = x (3x - 4) -2 (3x - 4) = (x - 2) (3x - 4) confidence rating #$&*: 3 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: * * ** Possibilities are (3x - 8) ( x - 1), (3x - 1) ( x - 8), (3x - 2) ( x - 4), (3x - 4) ( x - 2). The possibility that gives us 3 x^2 - 10 x + 8 is (3x - 4) ( x - 2). ** R.5.88 (was R.6.78). What do you get when you factor 14 + 6 x - x^2 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: First I flipped it around so that it read in order of highest degree to lowest degree. 14 + 6 x - x^2 = - x^2 + 6x + 14 = -1 (x^2 - 6x -14) I attempted to see if more factoring was possible by finding pairs of integers that had a product of -14 and added up to -6, but none met both criteria. This seems to be as far as the problem may be factored (prime) confidence rating #$&*: 2 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: * * ** This expression factors, but not into binomials with integer coefficients. We could list all the possibilities: (x + 7) ( -x + 2), (x + 2) ( -x + 7), (x + 14) ( -x + 1), (x + 1)(-x + 14) but none of these will give us the desired result. For future reference: You often cannot find the factors by factoring in the usual manner; however it is always possible to find the factors of a second-degree trinomial using the quadratic formula. The quadratic formula applied to this problem tells us that the factors are (x - z1) * (x - z2), were z1 and z2 are the solutions to the equation 14 + 6 x - x^2 0. Using the formula we find that z1 = ( -6 + sqrt(6^2 - 4 * 14 * (-1) )) / (2 * -1) and z2 = ( -6 - sqrt(6^2 - 4 * 14 * (-1) ) ) / (2 * -1) . Since sqrt(6^2 - 4 * 14 * (-1) ) = sqrt(36 + 56) = sqrt(92) is a real number these solutions are real numbers but again, as in a previous example, they aren't rational numbers and nobody could ever find them by inspection. This is not something you're expected to do at this point. ** " Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: R.5.64 (was R.6.60). What do you get when you factor 3 x^2 - 10 x + 8 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: Comparing it to Ax^2 + Bx + C we find that A= 3 B = -10 and C = 8 The value of AC = 24 We must find the pair of integers that result in 24 as their product; the possibilities are 1, 24; -1, -24; 2, 12; -2, -12; 3, 8; -3, -8; 4, 6; and -4, -6 We must find which of these pairs adds up to B. -4 and -6 result in a sum of -10 Applying this, 3 x^2 - 10 x + 8 = 3 x^2 - 4x - 6x + 8 = (3 x^2 - 4x) + (-6x + 8) = x (3x - 4) -2 (3x - 4) = (x - 2) (3x - 4) confidence rating #$&*: 3 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: * * ** Possibilities are (3x - 8) ( x - 1), (3x - 1) ( x - 8), (3x - 2) ( x - 4), (3x - 4) ( x - 2). The possibility that gives us 3 x^2 - 10 x + 8 is (3x - 4) ( x - 2). ** R.5.88 (was R.6.78). What do you get when you factor 14 + 6 x - x^2 and how did you get your result? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: First I flipped it around so that it read in order of highest degree to lowest degree. 14 + 6 x - x^2 = - x^2 + 6x + 14 = -1 (x^2 - 6x -14) I attempted to see if more factoring was possible by finding pairs of integers that had a product of -14 and added up to -6, but none met both criteria. This seems to be as far as the problem may be factored (prime) confidence rating #$&*: 2 ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: * * ** This expression factors, but not into binomials with integer coefficients. We could list all the possibilities: (x + 7) ( -x + 2), (x + 2) ( -x + 7), (x + 14) ( -x + 1), (x + 1)(-x + 14) but none of these will give us the desired result. For future reference: You often cannot find the factors by factoring in the usual manner; however it is always possible to find the factors of a second-degree trinomial using the quadratic formula. The quadratic formula applied to this problem tells us that the factors are (x - z1) * (x - z2), were z1 and z2 are the solutions to the equation 14 + 6 x - x^2 0. Using the formula we find that z1 = ( -6 + sqrt(6^2 - 4 * 14 * (-1) )) / (2 * -1) and z2 = ( -6 - sqrt(6^2 - 4 * 14 * (-1) ) ) / (2 * -1) . Since sqrt(6^2 - 4 * 14 * (-1) ) = sqrt(36 + 56) = sqrt(92) is a real number these solutions are real numbers but again, as in a previous example, they aren't rational numbers and nobody could ever find them by inspection. This is not something you're expected to do at this point. ** " Self-critique (if necessary): ------------------------------------------------ Self-critique rating: #*&!